The Generalised Local Model applied to Fibreglass. (15th October 2018) - Vantadori, Sabrina; Muñiz-Calvente, Miguel; Scorza, Daniela; Fernández-Canteli, Alfonso; Vázquez, Adrián Álvarez; Carpinteri, Andrea
Abstract: In the present research work, the Generalised Local Model (GLM) is employed to characterize the failure of a commercial Fibreglass by determining the Primary Cumulative Distribution Function of Failure (PCDFF) through an experimental campaign and numerical computations. Four criteria used to define the failure condition are based on the following Generalised Parameters (GPs): (i) Maximum Principal Stress; (ii) von Mises Stress; (iii) Tsai-Hill GP; (iv) Hoffman GP. For each GP adopted, the PCDFF is derived in two different ways: (a) by examining data obtained from tension tests only (GLM single application); (b) by collecting data, determined through tension tests and three-point bending tests, into a unique set (GLM joint application). Finally, a comparison between the obtained PCDFFs and the experimental failure results is presented.